Herbert J. Gans. Popular Culture & High Culture. An Analysis and Evaluation of Taste, Nueva York, Basic Books, 1999, 248 páginas. - Benzecry, Claudio E. (2000)
Fil: Benzecry, Claudio E. The City University of New York; Estados Unidos.